Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Ask your questions and receive precise answers from experienced professionals across different disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the inverse of the function \( f(n) = 2(n+2)^3 \), we need to follow a step-by-step algebraic procedure. Here's how we can do this:
1. Write the function in terms of \( y \):
\( y = 2(n + 2)^3 \)
2. Switch \( y \) and \( n \) to find the inverse function:
\( n = 2(y + 2)^3 \)
However, this approach should instead provide:
\( x = 2(n + 2)^3 \)
Here we are switching \( f(n) \) with the other variable to find the function's inverse, essentially treating \( x = f(n) \).
3. Solve for \( n \) in terms of \( x \):
\( x = 2(n + 2)^3 \)
Divide both sides by 2:
\( \frac{x}{2} = (n + 2)^3 \)
Take the cube root of both sides:
\( \sqrt[3]{\frac{x}{2}} = n + 2 \)
Subtract 2 from both sides:
\( n = \sqrt[3]{\frac{x}{2}} - 2 \)
Hence, the algebraic inverse of the function \( f(n) = 2(n + 2)^3 \) is:
[tex]\[ f^{-1}(x) = \sqrt[3]{\frac{x}{2}} - 2 \][/tex]
Now, let's examine the results that emerge when solving this equation. The inverse function in the answers presented includes:
1. \( \frac{2^{2/3}x^{1/3}}{2} - 2 \)
2. \( \frac{2^{2/3}x^{1/3}(-1/2 - \sqrt{3}i/2)}{2} - 2 \)
3. \( \frac{2^{2/3}x^{1/3}(-1/2 + \sqrt{3}i/2)}{2} - 2 \)
So, the correct inverse function in standard form for real numbers often simplifies as the first term:
[tex]\[ f^{-1}(x) = \frac{\sqrt[3]{x}}{\sqrt[3]{2}} - 2 \][/tex]
or equivalently,
[tex]\[ f^{-1}(x) = \sqrt[3]{\frac{x}{2}} - 2 \][/tex]
Thus, we have derived the proper form of the inverse function from the given scenario.
1. Write the function in terms of \( y \):
\( y = 2(n + 2)^3 \)
2. Switch \( y \) and \( n \) to find the inverse function:
\( n = 2(y + 2)^3 \)
However, this approach should instead provide:
\( x = 2(n + 2)^3 \)
Here we are switching \( f(n) \) with the other variable to find the function's inverse, essentially treating \( x = f(n) \).
3. Solve for \( n \) in terms of \( x \):
\( x = 2(n + 2)^3 \)
Divide both sides by 2:
\( \frac{x}{2} = (n + 2)^3 \)
Take the cube root of both sides:
\( \sqrt[3]{\frac{x}{2}} = n + 2 \)
Subtract 2 from both sides:
\( n = \sqrt[3]{\frac{x}{2}} - 2 \)
Hence, the algebraic inverse of the function \( f(n) = 2(n + 2)^3 \) is:
[tex]\[ f^{-1}(x) = \sqrt[3]{\frac{x}{2}} - 2 \][/tex]
Now, let's examine the results that emerge when solving this equation. The inverse function in the answers presented includes:
1. \( \frac{2^{2/3}x^{1/3}}{2} - 2 \)
2. \( \frac{2^{2/3}x^{1/3}(-1/2 - \sqrt{3}i/2)}{2} - 2 \)
3. \( \frac{2^{2/3}x^{1/3}(-1/2 + \sqrt{3}i/2)}{2} - 2 \)
So, the correct inverse function in standard form for real numbers often simplifies as the first term:
[tex]\[ f^{-1}(x) = \frac{\sqrt[3]{x}}{\sqrt[3]{2}} - 2 \][/tex]
or equivalently,
[tex]\[ f^{-1}(x) = \sqrt[3]{\frac{x}{2}} - 2 \][/tex]
Thus, we have derived the proper form of the inverse function from the given scenario.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.